2008
DOI: 10.1146/annurev.cellbio.24.110707.175250
|View full text |Cite
|
Sign up to set email alerts
|

Dscam-Mediated Cell Recognition Regulates Neural Circuit Formation

Abstract: The Dscam family of immunoglobulin cell surface proteins mediates recognition events between neurons that play an essential role in the establishment of neural circuits. The Drosophila Dscam1 locus encodes tens of thousands of cell surface proteins via alternative splicing. These isoforms exhibit exquisite isoform-specific binding in vitro that mediates homophilic repulsion in vivo. These properties provide the molecular basis for self-avoidance, an essential developmental mechanism that allows axonal and dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
158
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 51 publications
(88 reference statements)
4
158
2
Order By: Relevance
“…This implies that the γ-Pcdh EC1 domain might not directly participate in recognition, which is in agreement with data showing that EC1 from α-Pcdh-A4 has no adhesive properties (19). The requirement for both EC2 and EC3 in γ-Pcdh specificity is reminiscent of interactions between isoforms of Drosophila Dscam, in which homophilic binding specificity is determined by three alternatively spliced Ig domains, all of which must match for interaction to occur (44). Although our experiments focused on two isoforms, it is important to note that all chimeric γ-Pcdhs, including two that had hybrid EC2/EC3 pairs, were able to mediate homophilic cell aggregation comparably with that of WT proteins.…”
Section: Discussionsupporting
confidence: 85%
“…This implies that the γ-Pcdh EC1 domain might not directly participate in recognition, which is in agreement with data showing that EC1 from α-Pcdh-A4 has no adhesive properties (19). The requirement for both EC2 and EC3 in γ-Pcdh specificity is reminiscent of interactions between isoforms of Drosophila Dscam, in which homophilic binding specificity is determined by three alternatively spliced Ig domains, all of which must match for interaction to occur (44). Although our experiments focused on two isoforms, it is important to note that all chimeric γ-Pcdhs, including two that had hybrid EC2/EC3 pairs, were able to mediate homophilic cell aggregation comparably with that of WT proteins.…”
Section: Discussionsupporting
confidence: 85%
“…Studies of the Drosophila Dscam genes have elegantly demonstrated the importance of single-cell diversity of cell-surface proteins in neural circuit assembly (36). In this case, the diversity is generated by stochastic alternative pre-mRNA splicing of an extraordinarily complex pre-mRNA.…”
Section: Hs5-1 Enhancer Represses Pcdhα Expression In Nonneuronal Celmentioning
confidence: 99%
“…Specialized genetic mechanisms have evolved to generate this diversity. The Drosophila Dscam1 gene exemplifies one such mechanism, where alternative premRNA splicing generates 19,008 distinct extracellular protein interaction domains (2). This alternative splicing is stochastic; each neuron expresses multiple Dscam1 splice forms, and individual neurons express distinct combinations.…”
mentioning
confidence: 99%